2022
DOI: 10.4103/jcd.jcd_135_22
|View full text |Cite
|
Sign up to set email alerts
|

Value addition property of a cationic surfactant on endodontic irrigant: A confocal laser scanning microscope study

Abstract: Introduction: Chlorhexidine (CHX) is a commonly used root canal irrigant with high surface tension which prevents its penetration into the isthmus and fins of the root canal. Surfactants have known to reduce the surface tension of the liquid. Cetylpyridinium chloride (CPC) is a cationic surfactant. The aim of this study is to assess the contact angle formed and depth of penetration of the endodontic irrigant with and without the addition of surfactant. Methods: Contact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The combination of 2% CHX + 0.2% CPC was used as an endodontic irrigant for the first time by Thirunarayanan and Hegde [ 13 ] to overcome one of the CHX irrigant drawbacks, which is the high surface tension. The antimicrobial activity of this combination was assessed as mouthwash and in different concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The combination of 2% CHX + 0.2% CPC was used as an endodontic irrigant for the first time by Thirunarayanan and Hegde [ 13 ] to overcome one of the CHX irrigant drawbacks, which is the high surface tension. The antimicrobial activity of this combination was assessed as mouthwash and in different concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the earlier-stated result, the findings of this study was not consistent with Davis et al [ 15 ] and Mattigatti et al [ 34 ] who stated that MTAD showed more zones of inhibition and antimicrobial activity on E. faecalis than those of 2% CHX; this may be related to the differences in the methodology used for assessing the antimicrobial activities of the irrigants used in their studies for the agar diffusion test that is affected by the irrigant diffusibility, which is in turn affected by the irrigant surface tension [ 15 , 34 ]. MTAD has less surface tension than 2% CHX because of the presence of surfactant in its composition; therefore, it had more inhibition zones [ 13 ]. The present study was consistent with that of Agrawal et al [ 17 ], who stated that MTAD is more effective than 2% CHX, which may be related to the differences in the contact time between the microorganism and the irrigants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations